“An Eden that is practically uninhabited by humans”: Manipulating Wilderness in Managing Vancouver’s Drinking Water, 1880–1930 - Kuhlberg, Mark (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2016)
Vancouver is known internationally as one of the world’s most livable and beautiful cities, and its “natural” attributes are seen as being integral to what makes it so special. Nestled on a small plateau between the alluring beaches and dramatic shoreline of the Pacific Ocean and the Coast Mountain Range, the city has trumpeted its aesthetically stunning environment for over one century. Central to this message has been the fact that Vancouver’s drinking water supply is so clean that it has historically required no chemical or other treatment—besides a basic filtering—before it is fit for human consumption.Those who were initially responsible for administering the city’s water supply demonstrated most curious behaviour in carrying out their duties. To be sure, they exalted their water for its purity and broadcast this message to the world, believing as they did that such a precious resource could originate only in pristine wilderness that was as pleasing to the eye as it was free from human intrusions. As a result, they went to enormous lengths to guard the basins from which this water came from anthropogenic activity. Paradoxically, they were completely comfortable with undertaking a series of measures to re-engineer and manage the watersheds upon which they depended, an approach that included dumping tons of a deadly toxin on the local trees. All these steps were simply part of their efforts to enhance the bounty with which Providence had gifted them, and to them it remained pure and unsullied as a result. The early history of managing Vancouver’s drinking water thus represents an extraordinary instance in which civic boosters viewed their actions through a prism that blurred the line between the human and non-human worlds, and their story highlights how often our attempts to manage “nature” is prone to creating issues that are potentially more dangerous than the ones we are trying to solve.